Challenging hegemony, imaging alternatives. Everyday youth discourses and practices of resistance in contemporary Tunisia. Issue 2 (4th March 2021) - Cordova, Giovanni
ABSTRACT: Recent Maghreb conflicts and social transformation have shown the existence of disputes and complex negotiations over the moral economies that, in the national public consciousness, mobilise common adherence to norms and values. In this paper, I will consider the urban context of Tunis. Through an ethnography conducted among young Tunisians of middle and working classes (most of them having interrupted their advanced studies) I propose to find the features, even if ambiguous, of a moral economy that exists outside the hegemonic moral economy. By examining everyday practices and discourses, related to both the sacred and the profane poles of the social experience, I will try to provide a glimpse of the incubation of alternative political and social models among young Tunisians who are not engaged in politics or social movements. Does it represent a challenge to the dominant neoliberal political and cultural order or not?